Endometrial Receptivity Analysis (ARA) in Women with Repeated Implantation Failure (RIF) Under Intracytoplasmic Sperm Injection (ICSI): A Review - Hamid Mohan Al-Gawwam, Zahraa; Hamzah Abdulhussein, Rasha; Abd Al-Mahdi Ghazi, Hameda; K.H. Chabuk, Shahlaa (Hammurabi Journal of Medical Sciences, 2025)
Endometrial receptivity is the key factor of successful implantation that ties directly to achieving pregnancy. In many decades, well-meaning endeavors aimed at untangling the myriad biological mazes concerning not just endometrial receptivity but also embryo implantation have borne fruit in terms of knowledge. However, that knowledge does not translate into effective practices in the clinic and indeed actual challenges posed by Repeated Implantation Failure within the wider context of Assisted Reproductive Technology. Here, Intracytoplasmic sperm injection (ICSI) proved to be a significant helper where successful implanted embryos did not materialize over several attempts repeated implantation failure (RIF) varied greatly between different populations and was something eventually found out to be an extremely complicated etiology involving multiple factors. This literature review puts together all the study results about endometrial receptivity analysis, showing important markers, molecular interactions, and possible treatment plans; at the same time finding gaps in knowledge and suggesting paths for future study. It also combines recent research findings on endometrial receptivity analysis (ERA) and what it means for making outcomes better in women with RIF who are going through ICSI.